1983
DOI: 10.1080/03014223.1983.10423894
|View full text |Cite
|
Sign up to set email alerts
|

Morphometrics of forest birds in the Orongorongo Valley, Wellington, New Zealand

Abstract: Birds in indigenous forest in the Orongorongo Valley, Wellington, were mist-netted from 1967 to 1976, and 3902 were weighed and measured. Average weight and measurements are given for New Zealand pigeon, shining cuckoo, long-tailed cuckoo, morepork, New Zealand kingfisher, rifleman, hedgesparrow, whitehead, grey warbler, fantail, tomtit, song thrush, blackbird, silvereye, bellbird, tui, and chaffinch. In 5 species males and females were easily identifiable by plumage differences, and also differed in size. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…O'Donnell (1981) reported that the foods of kingfishers from three sites included many forest insects. Robertson et al (1983) included it in a discussion of forest birds from the southern North Island. Williams & Harrison (1972) suggested that the laughing owl was a bird ofrocky areas and the forest edge, but it has been recorded from forested areas of both the North and South islands.…”
Section: Species-area Relationshipsmentioning
confidence: 99%
“…O'Donnell (1981) reported that the foods of kingfishers from three sites included many forest insects. Robertson et al (1983) included it in a discussion of forest birds from the southern North Island. Williams & Harrison (1972) suggested that the laughing owl was a bird ofrocky areas and the forest edge, but it has been recorded from forested areas of both the North and South islands.…”
Section: Species-area Relationshipsmentioning
confidence: 99%
“…They were operated 4 days a month 1969-1976, except in the rain. This unique rig is described in Whitaker (1972), with results in Robertson et al (1983) and Fitzgerald et al (1989). Altogether, 3902 birds of 23 species were caught 5964 times.…”
Section: Bird Studies In the Orongorongo Valleymentioning
confidence: 83%
“…;Abbott 1977;Robertson & Woodall 1982). The New Zealand grey-backed white-eye (= silvereye) is heavier and has longer wings than the Fiji subspecies (Gill 1980;Robertson et al 1983). The Fijian scarlet robin has a significantly shorter wing (60 mm) (even allowing for shrinkage of museum specimens) than those from Southern Victoria and Tasmania (74-75 mm) (Abbott 1977).…”
Section: Discussionmentioning
confidence: 99%